Learning English Vocabulary Using Bingo Games For Early Age Children - Duta Utama; Nurul Aliya Zahra; Nurul Marqvirah; Rafli Nursa Esyam; Susilawati (Asosiasi Pengelola Publikasi Ilmiah (APPI) PT PGRI, 2024)
This study aims to investigate the effect of the Bingo game in introducing English vocabulary in Early Childhood. This research uses a qualitative method, with subjects consisting of young children who participate in Bingo game activities that are systematically arranged to introduce English vocabulary with a literature study approach. In which, through relevant data related to the subject matter, researchers collect, classify, process data to produce a new conclusion. Bingo games are an effective interactive strategy to improve children's vocabulary acquisition. In this study, we developed a Bingo game program specifically designed to improve children's language skills. The program engages children in a variety of engaging activities, such as searching for words that match a given picture or text. The results showed that children who participated in the Bingo game showed significant improvements in vocabulary acquisition and overall language skills. In addition, the game also increased children's learning motivation and engagement in the language learning process. Thus, the Bingo game can be an effective educational tool to improve children's vocabulary acquisition.